2016
DOI: 10.1111/jgh.13425
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness analysis of antiviral therapy in patients with advanced hepatitis B virus‐related hepatocellular carcinoma treated with sorafenib

Abstract: Based on the cost-effectiveness threshold ($20 301.00/QALY in China), addition of antiviral therapy to sorafenib is considered to be a cost-effective option compared with sorafenib monotherapy in patients with advanced HBV-related HCC in China from the patient's perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…These findings suggest that sorafenib resistance in HCC may be attributable to the compensatory effects in response to the activated PI3K/AKT signaling pathway. In addition, Zhang et al (2016b) further indicated that phosphorylation-activated FAK participates in the activation of the PI3K/AKT signaling pathway when sorafenib resistance occurred in HCC cells. FAK is an aberrantly highly expressed cytoplasmic protein tyrosine kinase that can facilitate the progression and metastasis of HCC (Chen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that sorafenib resistance in HCC may be attributable to the compensatory effects in response to the activated PI3K/AKT signaling pathway. In addition, Zhang et al (2016b) further indicated that phosphorylation-activated FAK participates in the activation of the PI3K/AKT signaling pathway when sorafenib resistance occurred in HCC cells. FAK is an aberrantly highly expressed cytoplasmic protein tyrosine kinase that can facilitate the progression and metastasis of HCC (Chen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Costs for managing grade 3‐4 AEs weighted by frequency were calculated based on the use of amlodipine 5 mg daily for hypertension, Eucerin cream for hand–foot syndrome and atropine/diphenoxylate and loperamide for diarrhoea . These costs were sourced from published literature, the Red Book, the British National Formulary and Chinese national drug prices . All costs were converted to 2017 US dollars at exchange rate of 1USD = 0.7075GBP and 1USD = 6.8RMB .…”
Section: Methodsmentioning
confidence: 99%
“…Utility coefficients were retrieved and an average value was derived for each health state in the model [27][28][29][30][31][32][33]. For the toxicity and complications that are transient, we assumed that there was a lower utility for TACE plus SBRT with a multiplier 0.9.…”
Section: Quality-of-life Estimatesmentioning
confidence: 99%